Case reportEndolymphatic sac tumour (ELST). Case report of a rare tumour of the temporal bone, presenting as a mass in a cerebello-pontine angle - Czopek, Jacek; Waśko, Marcin; Adamek, Dariusz (Folia Neuropathologica, 2013)
Endolymphatic sac tumour (ELST) is a primary low-grade, locally invasive adenocarcinoma of the endolymphatic sac, charac- terized by the proliferation of cuboidal cells forming a papillotubular pattern and colloid-filled cysts. Rare in the general population, it coincides significantly with the presence of von Hippel-Lindau disease. The natural history, mechanisms underlying the early symptoms, anatomical origin of ELST and optimal timing of their treatment are unknown. In this study, we report a Polish male patient with sporadic ELST (without a family history of VHL disease) along with a review of literature. The light microscopic and immunohistochemical features as well as clinical presentation were typical of ELST.